L'adoption coutumière inuit au Nunavik et le comportement de l'enfant à l'âge scolaire - Decaluwe, Béatrice (Université Laval, 2016)
The focus of this doctoral thesis is on Inuit customary adoption in Nunavik. The main objective is to study the association between customary adoption practices and child behavioral problems at school-age. In Nunavik, one-third of Inuit children are adopted according to customary adoption practices. The first article describe the cultural context and the main characteristics of Inuit customary adoption. Taking place at birth, customary adoption is considered as the donation of a child to a close kin, usually the parent’s sibling or the child’s grandparent. Contrary to closed adoptions which is in standard legal use in southern Canada and in the USA, customary adoption is not confidential and biological ties are not severed. The actual information on the development of Inuit adopted children come from a limited body of studies on Inuit children followed by youth protection services. Using data from a prospective longitudinal study conducted in Nunavik, this thesis included a sample of 46 adopted and 231 non-adopted children followed from birth to school age. Prenatal and familial informations were collected and behavioral problems were assessed using the Teacher Report Form of the Child Behavior Checklist. The second article compare adopted and non-adopted children on prenatal and familial characteristics and examine the actual extent of the increase in the number of behavior problems seen in Inuit children adopted in accordance with Inuit customs. Adoption per se is not associated with higher rate of behavioral problems at school age but adopted and non-adopted Inuit children were raised in significantly distinct family environments at school-age. Given such differences, the last article identified the prenatal and familial risk factors associated with attention problems and externalizing behaviors in a subsample of Inuit adopted children (n=46). Attention and externalizing behaviors were better explained by familial variables at school age than by prenatal variables. These results contrast significantly with ...